Women and Family Based Voter Education Strategy to Increase Community Participation in Elections in Buton, Indonesia - Kadir, Abdul; Burhan, Burhan; Mahrudin, Mahrudin; Sumardona, Sumardona (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This article discusses women and family-based voter education strategies to increase community participation in regional elections in Buton, Southeast Sulawesi, Indonesia. Voter education plays an important role in strengthening democracy and generating public interest, then women and families are important segments in the context of political participation in Indonesia. This study uses qualitative methods, analyzed with political participation theory. Data was collected by means of document study and interviews. The documents analyzed refer to articles, books, scientific reports and various studies related to the discussion, while the informants interviewed are women voters and their families. This study concludes that as an election organizer, the KPU at the district/city level can adopt the concept of a social learning framework to observe the configuration and dynamics in organizing elections. Social learning involves commissioners and the public in learning from peers, first-time voters, and available resources. Political education can also strengthen democratization efforts and overcome negative perceptions of politics. Voter education plans must consider the development of autonomy, open-mindedness, efficiency, transparency, and popular or non-formal education. To increase community participation in elections, women and their families must maximize their role as segments of voters who are close to the community. According to political participation theory, one effective strategy to increase political participation is elections that involve women and families so that people's voices can be meaningful in building democracy.